Iowa Birdline update, October 16, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for October 16, 1989. Highlights include a winter plumaged Lesser Black-backed Gull standing with Herring Gulls. Epson - sheet feed/flatbed